Analisis Efek Mediasi Stres Kerja dalam Hubungan Beban Kerja dan Kepuasan Kerja Karyawan - Tinambunan , Hanna Rosa Laura (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the mediating effect of work stress in the relationship between workload and employee job satisfaction. The research employs a quantitative approach using a census technique involving all 44 permanent employees. This study employs Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study show that: (1) workload does not have a significant effect on job satisfaction, as indicated by a coefficient value of 0.149, t-value of 0.583 < t-table of 1.96, and a significance value of 0.560 > 0.05, (2) workload has a positive and significant effect on job stress, with a coefficient of 0.617, t-value of 3.093 > t-table of 1.96, and a significance value of 0.002 < 0.05, (3) job stress has a negative and significant effect on job satisfaction, with a coefficient of -0.572, t-value of 3.093 > t-table of 1.96, and a significance value of 0.001 < 0.05, (4) workload has a negative and significant indirect effect on job satisfaction through job stress, with a coefficient of -0.353, t-value of 2.180 > t-table of 1.96, and a significance value of 0.029 < 0.05.